The process of selection of the main research methods in foresight from different perspectives - Magruk, Andrzej (Business, Management and Economics Engineering, 2015)
When making research tasks in every field of science is essential to have the conviction that the selected research methods and procedures are reasonable applied, that is, one that effectively lead to the realization of the defined tasks. The set of methods that can be used in foresight projects (future studies) is very rich and, due to the dynamics of foresight, is still open. This article presents a synthetic set of guidelines for the choice of methods for exploring the future, paying attention to the very important fact that the rules of effective methodical conduction, due to its complexity, are often not clearly defined. Depending on the context, functions, stages, types, classes of foresight methods can be used in different ways, which also complicates the creation of optimum model. The article shows that this problem – under certain conditions – can be effectively minimized. The article analyzes the current (shown in the future science literature) approaches, principles, assumptions associated with the selection of foresight research methods.